Effect of Non-Pharmacological Pain Management Program on Nurses Performance and Patient Clinical Outcomes Undergoing Cardiothoracic Surgery (Cuestiones de Fisioterapia, 2024)
Background: Non-pharmacological measures are an important part of pain management that is used by critical care nurses to increase the tolerance of experienced pain, decrease physical stress. The study aimed to evaluate the effect of non-pharmacological pain management program on nurses’ performance and patient clinical outcomes undergoing cardiothoracic surgery Research design: A quasiexperimental research design was conducted.